Pembiasaan Akhlak Terpuji pada Anak Tunagrahita di SMPLB Kanigoro Kras Kediri - Khoulita, Ikhfi (Didaktika Religia, 2014)
This study will examine how moral habituation in children with some intellectualimpediments takes place. The location of the study is SMPLB Kanigoro, Kras,Kediri. This study uses a qualitative research method by using interviews,observation and documentation. The results show that the method (habituation)could be a means of forming moral habit for children with limited intelligencedevelopment. With these characteristics, the education provided must adapt to thesituation of children with some intellectual impediment.